2019
DOI: 10.1111/1754-9485.12884
|View full text |Cite
|
Sign up to set email alerts
|

Contour variation is a primary source of error when delivering post prostatectomy radiotherapy: Results of the Trans‐Tasman Radiation Oncology Group 08.03 Radiotherapy Adjuvant Versus Early Salvage (RAVES) benchmarking exercise

Abstract: Introduction Variation in target volume delineation from clinical trial protocols has been shown to contribute to poorer patient outcomes. A clinical trial quality assurance framework can support compliance with trial protocol. Results of the TROG 08.03 RAVES benchmarking exercise considering variation from protocol, inter‐observer variability and impact on dosimetry are reported in this paper. Methods Clinicians were required to contour and plan a benchmarking case according to trial protocol. Geometric pjmir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In RT, differences in OAR volumes do not always translate into large dose differences [9] , [21] although compliance to trial protocols have been reported to be compromised due to incorrect delineations [2] . We found in our data that autosegmented rectal volumes, irrespective of algorithm version, were overall closer to the manually-delineated uncurated clinical rectal volumes (Δ≈0.5–1 cm 3 ) than to the manually-delineated curated rectal volumes (Δ≈1-3 cm 3 ), with the larger differences typically generated by the smaller-sized training datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RT, differences in OAR volumes do not always translate into large dose differences [9] , [21] although compliance to trial protocols have been reported to be compromised due to incorrect delineations [2] . We found in our data that autosegmented rectal volumes, irrespective of algorithm version, were overall closer to the manually-delineated uncurated clinical rectal volumes (Δ≈0.5–1 cm 3 ) than to the manually-delineated curated rectal volumes (Δ≈1-3 cm 3 ), with the larger differences typically generated by the smaller-sized training datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In radiation therapy (RT), contour/volume variability continues to be a problem, in particular for non-tumour tissue or organs at risk (OARs) [1] , [2] , [3] , [4] , [5] . Dose fall-off margins in modern RT can be set extremely tight meaning that correct volume definitions are more critical now compared with previous RT delivery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Contouring variation is a common weakness in RT trials. [6][7][8] Marked variations in target volumes and organ-at-risk (OAR) delineations for breast cancer have been reported. 9,10 Computed tomography (CT)−based RT planning for breast cancer has not been applied widely until recent years; therefore, studies on pretrial target delineation QA in breast cancer are limited, 11,12 and no slice-by-slice analysis has been undertaken to identify the details of contouring variation.…”
Section: Introductionmentioning
confidence: 99%
“…Variability in contouring is deemed to be one of the greatest sources of error in medical dosimetry [6]. Previous studies have stated that variations in contouring can be occurred in health professionals with different level of experience [7][8][9].…”
Section: Introductionmentioning
confidence: 99%